Réécritures migrantes de quelques classiques de la littérature québécoise : jalons vers un nouveau «texte national»? - Smart, Patricia (Romanica Silesiana)
The article draws attention to the phenomenon of rewritings of works belonging to the Québécois literary canon by authors born outside the country, yet educated in Quebec. It indicates a significant contribution of immigrant writers to the breaking down of borders between canonical works and so called immigrant writing. The paper focuses on the similarities in theme, structure and imagery between Bianca Zagolin’s “Une femme à la fenêtre” and Louis Hémon’s “Maria Chapdelaine”, as well as Gabrielle Roy’s “Bonheur d’occasion” and Abla Farhoud’s “Le Bonheur a la queue glissante”. Through the penetration of the canon and “écriture migrante”, a new, ‘national text’ is born. Key words: immigration; rewriting; national text; intertextuality